Efektivitas Police to Police Cooperation Kepolisian Republik Indonesia dengan Kepolisian Filipina dalam Memberantas Tindak Kejahatan Penyelundupan Senjata Api Ilegal - Jasmin Michael Gultom; Tri Cahyo Utomo (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
Illegal arms smugglings is a crime that possessed a tangible threat. An act of brought infirearms illegally from one territory to another will ignite threats to the destined territory.Crimes such as armed robbery, armed vigilante action and terrorism are frequentphenomena appeared followed by the increasing spread of illegal firearms in a region.Preventing crimes that resulted from illegal firearms and eradicate illegal arms smugglingare police main objectives. The firearms that need to be eradicate came from Philippinesand smuggled to Indonesia. Those illegal firearms contributed armed criminals from streetthugs all the way to organized terrorist group. Cooperation between Indonesia NationalPolice and Philippines National Police is an effective solution to eradicate widespread ofillegal firearms from Philippines. Knowing how effective the cooperation betweenIndonesia and Philippines police force is the main purpose of this research. Utilizeliberalism theory on viewing cooperation and police to police cooperation concept,researcher seeks the answer from formulation of the problem that questioning of howeffective the cooperation.